คุณภาพชีวิตการทำงานของบุคลากรในโรงพยาบาลวัดจันทร์เฉลิมพระเกียรติ 80 พรรษา อำเภอกัลยาณิวัฒนา จังหวัดเชียงใหม่ - ศิริพรรณ ทรงคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The Independent Study on The Quality of Working Life of Staff in Wat Chan 80th Celebrations Hospital, Kalyaniwattana District, Chiang Mai Province was aimed to study the level of quality of working life, to study work motivation, and to study the correlation between work motivation, work behavior and the quality of working life of staff in Wat Chan 80th Celebrations Hospital, Kalyaniwattana District, Chiang Mai Province. The populations used in research were a total of 64 personnel that consisted of government officials, government employees, The Ministry of Public Health staff, and temporary employees who worked in Wat Chan 80th Celebrations Hospital, Kalyaniwattana District, Chiang Mai Province. The research instrument was a questionnaire which was divided into 5 parts as 1) general information of the respondents 2) the quality of working life 3) work motivation 4) work behavior 5) opinion and suggestion about the quality of working life. Data were analyzed by a statistical software package. The statistics used in this research were Frequency, Percentage, Mean, Standard Deviation, and Spearman Rank Correlation Coefficient. The findings showed most hospital staff had the quality of working life at a high level. When considering four factors found that there were three factors with a high level of opinion that consisted of the safety and health conditions at work (3.48 %), the interaction and relationship between colleagues within organization (3.67 %), and the balance between career and lifestyle (3.65 %). The factor with a medium level of opinion was obtaining fair and adequate compensation (3.26 %). By the way, the averages of all factors were not much different. The level of work motivation of hospital staff in Wat Chan 80th Celebrations Hospital indicated that most hospital staff had a high level of work motivation. When considering three factors revealed that all factors were in a high level of opinion that consisted of the ability to recognized the results of task (3.43%), a sense of meaningful work (3.48 %), and responsibility (3.69 %). By the way, the averages of all factors were not much different. The correlation between work motivation, work behavior and the quality of working life was a moderate positive relationship with .00 of significant (r =0.566) that might be because work motivation and work behavior had the positive correlation with the quality of working life in all parts.